2020
DOI: 10.1021/acs.analchem.0c01854
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ordered Pt Nanocube Arrays Directed by Block Copolymer Nanotemplate and Their Potential on Ethanol Oxidation Reaction

Abstract: In this work, well-ordered platinum (Pt) nanocubes (NCs), with precise control on the size and the spatial arrangement, are synthesized from a microemulsion overgrowth in a block copolymer (BC) nanotemplate. The nanovials on this self-assembled BC template serve as microreactors for the reduction of the HCl/H 2 PtCl 6 precursor and direct the ordered periodic arrangement of the reduced Pt nanoparticles (NPs). As the content of HCl increases from 0% to 25%, the Pt NPs evolve from quasi-spheres to NCs, for which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…[42] Such exposed facets played an important role in the AORs. For example, the highly exposed crystal facets of Pt (100), (310), and (410) exhibited better AOR performance in comparison with the Pt (111) facet, [43] stemming from their stronger adsorption capability toward OH species. [43,44] Last but not least, these core-shell catalysts accelerate electron transfer rates at their interfaces, which are again much benefit for the AORs.…”
Section: Introductionmentioning
confidence: 99%
“…[42] Such exposed facets played an important role in the AORs. For example, the highly exposed crystal facets of Pt (100), (310), and (410) exhibited better AOR performance in comparison with the Pt (111) facet, [43] stemming from their stronger adsorption capability toward OH species. [43,44] Last but not least, these core-shell catalysts accelerate electron transfer rates at their interfaces, which are again much benefit for the AORs.…”
Section: Introductionmentioning
confidence: 99%
“…The SEM image of a PtCo/BCP nodule is provided in Figure b, which shows that the higher PtCo core is surrounded by the lower flat polymer domains. Subsequently, the polymer can be removed and the PtCo alloys will be simultaneously reduced under the H 2 /Ar plasma. , The center-to-center distance and the average diameter are ∼43 and ∼22 nm, respectively (Figure c). Note that the hexagonally arranged PtCo NPs (in Figure c) are consistent with the parent PtCo/BCP nodules (in Figure a), indicating that the self-assembly of the BCP directs the PtCo NPs into ordered nanoarrays.…”
Section: Resultsmentioning
confidence: 99%
“…Integrating with other metals to prepare Pt–M alloys is one feasible way to address these difficulties for the Pt-based catalysts. Core–shell structure NPs with Pt as shells attract much attention for the low Pt loading and the promotion on ORR activity. However, most of the core–shell NPs are prepared by solution-phase synthesis requiring complicated conditions. The template- and scaffold-assisted fabrication of NP arrays through block copolymers (BCPs) interests researchers with the large-scale morphologies in controllable distributions, shapes, and sizes. The microphase segregation of BCP blocks can compartmentalize the NPs into the interfaces between the different polymer chains or the microdomains of the polymers. As a result, the BCP approach is capable of fabricating highly ordered metal NP arrays fulfilling the requirements for a variety of practical applications. …”
Section: Introductionmentioning
confidence: 99%
“…29 For example, it has been reported that hexagonally arranged Pt nanocubes could be generated and that they demonstrate improved electrochemical activities towards ethanol oxidation reduction. 30 In most cases, a single kind of metallic NP was employed with precise control over the size and the shape of the resulting structures as well as the periodicity and symmetry of the structural patterns. 31…”
Section: Introductionmentioning
confidence: 99%